Combined effect of acid-sensing ion channel 3 and transient receptor potential vanilloid 1 gene polymorphisms on blood pressure variations in Taiwanese - Leay-Kiaw Er; Ming-Sheng Teng; Semon Wu; Lung-An Hsu; I-Shiang Tzeng; Ching-Feng Cheng; Hsin-I Chang; Hsin-Hua Chou; Yu-Lin Ko (Tzu Chi Medical Journal)
Objectives: Both acid-sensing ion channel acid-sensing ion channel 3 (ASIC3) and transient receptor potential vanilloid 1 (TRPV1) have been proposed to be involved in the pathophysiology of hypertension. Common colocalization of ASIC3 and TRPV1 channels in the same sensory neuron has been reported. We aimed to study the combined ASIC3 and TRPV1 gene polymorphisms in the risk of hypertension. Materials and Methods: To test the statistical association between genetic polymorphisms of the ASIC3 and TRPV1 genes and blood pressure (BP) variations in Taiwanese, 551 unrelated individuals (286 men and 265 women) having routine health examinations were recruited. The participants had no history of cardiovascular disease or use of medication for hypertension. Results: Six ASIC3 and four TRPV1 gene polymorphisms were genotyped, and only the ASIC3 rs2288646 polymorphism was associated with variations in BP in the participants. In subgroup analysis, we found participants carrying the combined ASIC3 rs2288646 AA or AG and TRPV1 rs8065080 CC genotypes (combined genotypes) had significantly higher systolic, mean and diastolic BP compared with the other subgroups (P = 0.009, 0.003, and 0.006, respectively, after Bonferroni correction). Interaction analysis also revealed significant gene-gene interaction in the systolic, mean, and diastolic BP in the ASIC3 and TRPV1 genotypes (interaction P = 0.006, 0.002, and 0.002, respectively). A trend of increasing frequencies of the combined genotype was observed in normotensive, prehypertensive, and hypertensive subgroups (P for trend = 0.001), as well as in those with higher systolic and diastolic BPs (P for trend = 9.13 × 10−4 and P for trend = 5.5 × 10−5, respectively). Conclusion: Our data show a combined effect of ASIC3 and TRPV1 gene polymorphisms in BP variations in Taiwanese. These results suggest that the interaction between ASIC3 and TRPV1 is involved in BP regulation.